The Influence of Economic Literacy on Consumptive Behavior of Pharmacy Students, Faculty of Mathematics and Natural Sciences, Cenderawasih University in Online Stores - Westi Setiati; Yulita Flaviana Bahy; Asdiana Dua Sumban; Chard Wali; Melpin Kasipmabin (PT. Intelek Cendikiawan Nusantara, 2024)
Consumptive behavior among students is an increasingly important issue to study, considering that this age group is in a transition phase from financial dependence to independence. One important factor that is thought to influence student consumption behavior is economic literacy. Economic literacy is an individual's knowledge and skills in understanding basic economic concepts, such as money management, savings, investment, and making wise financial decisions. It is important to conduct this research to identify the extent to which economic literacy influences students' consumptive behavior in online stores. The sample consisted of 50 students majoring in Pharmacy, Faculty of Mathematics and Natural Sciences. Data collection used a questionnaire with 20 questions. The data obtained will be analyzed using multiple linear regression and classical assumption tests and hypothesis testing will be carried out. The R Square value obtained was 0.113. This means that the influence of economic literacy on the consumer behavior variable is 11.3% and 88.7% is influenced by other variables.